(untitled) (Research, Society and Development, 2019)
Considering the constant requirement to improve, expand and consolidate efficient methods to protect metallic parts from corrosive processes, this research had the objective of evaluating the efficiency of the aqueous extract of purple ipê peels as potential corrosion inhibitor for carbon steel (P110) and stainless steel (22% Cr duplex), using hydrochloric acid as a corrosive medium. The inhibition efficiency of the extract was obtained from the corrosion rates of the steels identified by gravimetric tests. For carbon steel, the extract presented inhibition efficiency of 89.26%, using a concentration of 2.5 g/L of the extract, while for stainless steel the inhibition efficiency was 74.94%, for a concentration of 3.0 g/L extract. Adsorption isotherms were plotted with Frumkin’s, showing the best fit for the two steels, the DG adsorption values of -19.56 K.J.mol-1 and -15.92 K.J.mol-1 for carbon and stainless steel, indicating a spontaneous process of physical adsorption.